PERAN BADAN PENGAWAS PEMILU DALAM MENJAGA KEADILAN DAN TRANSPARANSI: TINJAUAN HUKUM ADMINISTRASI: The Role Of The Election Supervisory Agency In Maintaining Fairness And Transparency: A Review Of Administrative Law - Ariansyah Eka Saputra (ABISATYA DINAMIKA ISWARA, 2024)
The Election Supervisory Agency (Bawaslu) has a crucial role in maintaining fairness and transparency in the election process in Indonesia. As an institution responsible for supervising the implementation of elections, Bawaslu plays a role in preventing, detecting, and cracking down on violations that can threaten the integrity of democracy. This study aims to analyze the role of Bawaslu in the perspective of administrative law, focusing on the mechanism of supervision, law enforcement, and obstacles faced in carrying out its duties. The research method used is a normative juridical approach with an analysis of related laws and regulations, court decisions, and case studies on the implementation of election supervision. The results of the study show that although Bawaslu already has broad authority, there are still challenges in the effectiveness of law enforcement, such as limited resources and uncertainty in the implementation of administrative sanctions. This study emphasizes that strengthening regulations and increasing the institutional capacity of Bawaslu is needed to ensure fairer and more transparent elections. Thus, administrative law reform in the election supervision system is a strategic step to strengthen democracy in Indonesia.